Bar mitzvah : a history - Hilton, Michael (Lincoln ; London : University of Nebraska Press, 2014)
"The Jewish coming-of-age ceremony of bar mitzvah was first recorded in thirteenth-century France, where it took the form of a simple statement by the father that he was no longer responsible for his thirteen-year-old son. Today, bar mitzvah for boys and bat mitzvah for girls are more popular than at any time in history and are sometimes accompanied by lavish celebrations. How did bar mitzvah develop over the centuries from an obscure legal ritual into a core component of Judaism? How did it capture the imagination of even non-Jewish youth? Bar Mitzvah is a comprehensive history of the ceremonies and celebrations for both boys and girls. As cultural anthropology informed by rabbinic knowledge, it explores the origins and development of the most important coming-of-age milestone in Judaism. Rabbi Michael Hilton has sought out every reference to bar mitzvah in the Bible, the Talmud, and numerous other Jewish texts spanning several centuries, extracting a fascinating miscellany of information, stories, and commentary."--
"How the bar mitzvah developed over the centuries from an obscure legal ritual into a core component of Judaism and how it captured the imagination of everyone, including many non-Jewish youth"--
How bar mitzvah began -- How bar mitzvah became popular -- The spread and regulation of bar mitzvah -- Jewish confirmation -- Into the modern age -- Current issues and trends -- The evidence assessed.
"Published by the University of Nebraska Press as a Jewish Publication Society book."
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Bar mitzvah; RELIGION -- Judaism -- Rituals & Practice; SOCIAL SCIENCE -- Jewish Studies; RELIGION -- Judaism -- General; Bar mitzvah; Bar Mitswa; RELIGION / Judaism / Rituals & Practice; Electronic books